Configurações identitárias na arte contemporânea : a Bienal de São Paulo, de 1998 - Silva, Luiza Helena Oliveira da (2006)
The present thesis analyses texts and works of art belonging in the four catalogues of the XXIV Bienal de São Paulo, held in 1998, in that city. The Manifesto Antropófago, by Oswald de Andrade (1928) was chosen as the theme of the event. Thus, the trustees selected works from different countries and organized them under various perspectives raised by multiple views on anthropophagi and cannibalism. If, on the one hand, the reading on the present day of the inspiring text of the Semana de Arte Moderna raise queries about the claim of a national identity in the field of arts, the trustees enhance in the other hand these complex relations therefore, the exhibition questions, the process that involve economical domination, as the case of African artists, that disclose the violence exploitation process carried out in that continent until forms of dialogue between works of art from distinct origins and historical moments, using varied definitions such as contamination, insertions, punctuations, presences. More over, the considerations raised by the Bienal point out to, ultimately, to love relationships, blurring and intercultural dimensions, to the blurring of territorial frontiers and the erasing of the subject in the big urban centers, pointing the complexities involved in the identity and otherness relations in contemporary scenario. The corpus is constituted by texts (produced by Brazilian and foreign trustees, as well as essays, poems, fragments of texts by other authors, selected by the trustees) and reproductions of the formerly referred works, both part of the Bienal s catalogue. The presupposition that guides the present reading is the assumption that the identity claimed by the Brazilian Modernists in the first half of the XX th century, once elected as a theme, gains news meanings produced by contemporary artists. Once discourses on globalization claim for a new world order, the reconfiguration of power and decentralization of the nation states, productions and reflection on contemporary art point out new meanings for the motion of national , new identitary shapes. As theorical support, the thesis selected the discursive semiotics. As a theory of all languages and systems of signification, semiotics supports the reading of verbal and nonverbal texts, affording considerations in which the underlying principle is syncretism, on the effects of meaning produced by crossing of different languages since the analysis of discourses on contemporaneity is a priority, and thus the aspects related to ideology are privileged, the thesis also benefits from the contribution of French Discourse Analysis and theories arming at globalization and identity.